2013
DOI: 10.1002/ajoc.201200179
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Redox Properties of Photochromic Diarylethenes by Introducing Electron‐Withdrawing Substituents

Abstract: A series of seven photochromic diarylethenes (DAEs) with various electron‐withdrawing substituents and their respective closed‐form isomers (DAEC) were synthesized and the optical and redox properties of these photochromes were investigated by UV/vis absorption spectroscopy and cyclic voltammetry. Our comparative studies with these DAEs revealed that the absorption properties of the closed forms and the redox potentials of the open and closed isomers appreciably depend on the number and nature of the electron‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Thus, a strongly electron-deficient substituent such as pyridinium is necessary to shift the reduction potential to accessible values. However, not every electron-withdrawing group appears to be suited to induce cathodic cyclization [ 40 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a strongly electron-deficient substituent such as pyridinium is necessary to shift the reduction potential to accessible values. However, not every electron-withdrawing group appears to be suited to induce cathodic cyclization [ 40 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The reduction potential has strongly related to the kind of the substituent and their position . It is reported that the reduction potential of organic molecules becomes higher when the electron withdrawing substituent is placed . The overall trend of the reduction potential that increase with the electron withdrawing group is confirmed for these metal complexes.…”
Section: Resultsmentioning
confidence: 55%
“…The organic phase was extracted with ether (3 × 50 mL), and the organic layers were collected, washed with brine (2 × 50 mL), dried over MgSO 4 , filtered, and evaporated under vacuum. The resulting mixture was purified by flash column chromatography (100% hexane) to give 4 as a yellow solid (3.62 g, 62%) as mixture of parallel (p) and antiparallel (ap) isomers in a ratio of 36:64; mp 153–154 °C [lit . 154–156 °C].…”
Section: Methodsmentioning
confidence: 99%
“…The resulting mixture was purified by flash column chromatography (100% hexane) to give 4 as a yellow solid (3.62 g, 62%) as mixture of parallel (p) and antiparallel (ap) isomers in a ratio of 36…”
Section: 3'-(perfluorocyclopent-1-ene-12-diyl)bis(2-methylbenzothiophene) (4)mentioning
confidence: 99%